Neuroprotective effect of Ziziphus spina-christi on brain injury induced by transient global cerebral ischemia and reperfusion in rat - Setorki, Mahbubeh; Hooshmandi, Zahra (Bangladesh Journal of Pharmacology, 2017)
This study evaluated the protective effect of Ziziphus spina-christi on the cerebral oxidative stress and damage induced by ischemia. Male Wistar rats were divided randomly into six groups (seven in each group): Control group did not undergo surgery and received distilled water; shame group underwent surgery without ischemia; ischemic group underwent ischemia without any medication; extract-treated groups underwent ischemia and orally received 50, 100, 200 mg/kg/day doses Z. spina-christi extract. After behavioral tests, anti-oxidant capacity and malondialdehyde level of brain and serum were determined. Treatment of ischemic rats with extract significantly increased the frequency of passes through the hidden platform. Z. spina-christi improved motor coordination and balance. Administration of the extract into the ischemic rats prolonged the shortened step-through latency. Z. spina-christi extract significantly reduced the malondialdehyde level of brain and serum and improved serum and brain anti-oxidant capacity.